Enforcement of banking regulation and the cost of borrowing - Yota Deli; Manthos D. Delis; Iftekhar Hasan; Liuling Liu (Bank of Finland, 2018)
We show that borrowing firms benefit substantially from important enforcement actions issued on U.S. banks for safety and soundness reasons. Using hand-collected data on such actions from the main three U.S. regulators and syndicated loan deals over the years 1997-2014, we find that enforcement actions decrease the total cost of borrowing by approximately 22 basis points (or 4.6 million interest for the average loan). We attribute our finding to a competition-reputation effect that forces banks to lower their cost of credit, irrespective of other changes in their business models after the enforcement action.
URN:NBN:fi:bof-201810182096
Keywords: E44; E51; G21; G28; 330